Transcriptome and Resistance-Related Genes Analysis of Botrytis cinerea B05.10 Strain to Different Selective Pressures of Cyprodinil and Fenhexamid - Wang, Xuegui; Gong, Changwei; Zhao, Yun; Shen, Litao (Frontiers in Microbiology, 2018)
The pathogen Botrytis cinerea is a very dangerous pathogen that infects many economically important crops such as grape, strawberry, tomato, and eggplant. Cyprodinil, a pyrimidine amine fungicide, and fenhexamid, an amide fungicide, are new reagents for controlling gray mold with special efficacy. It is necessary to understand the change trends in the toxicological and physiological characteristics of B. cinerea with successive selective pressures of cyprodinil and fenhexamid to elongate the serving life of these fungicides for effective disease control. The toxicities of cyprodinil and fenhexamid at successive concentrations of EC25, EC50 and EC75 on B. cinerea strain BO5.10 were assayed along with mycelial growth-inhibition capacity. The results showed that the EC50 value of the cyprodinil-treated F27 strain increased approximately 18-fold, whereas of which in the fenhexamid-treated F27 strain increased only 3-fold compared with that of the F0 strain. The conductivities and glycerinum contents of the strains resistant to cyprodinil and fenhexamid were obviously enhanced; in contrast, the oxalic acid contents were decreased compared with those in the F0 strain. The transcriptomes of the F27 control (T01), cyprodinil-treated (T02) and fenhexamid- treated (T03) strains were analyzed, and the expression levels of functional genes in the T02 and T03 strains were significantly increased compared with those in the T01 strain; these results were further validated using qRT-PCR. The results indicated that the relative expression of two genes encoding mixed-functional oxidases (MFOs) BC1G_16062 and BC1G_16084, two genes encoding transmembrane proteins BC1G_12366 and BC1G_13768, two genes encoding Zinc finger proteins BC1G_13764 and BC1G_10483,one gene encoding citrate synthase enzyme BC1G_09151, one gene encoding gluconolactonase BC1G_15612 in the T02 and T03 strains and one gene encoding lysophospholipids enzyme BC1G_04893 in the T3 strain increased substantially compared with that in the T1 strain (P< 0.01). Functional prediction analysis of upregulated gene expression and structural verification was also performed, and the results showed that BC1G_10483 was a ZnF_C2HC transcriptional regulator interacting with the Sp1 element of these genes to respond to the pressures from cyprodinil and fenhexamid. Our results could contribute to a better understanding of the resistance mechanism of B. cinerea against cyprodinil and fenhexamid.